Linking Cultural Intelligence and Perceived Organizational Justice to Turnover Intention in the Lebanese Hospitality and Tourism Industry - Abi Abdallah, Sarah (2020)
Purpose: The everlasting search for reducing turnover remains present and on-going in the world of business especially in the hotel and tourism industry, where turnover rates are extremely high. The primary aim of this study is to assess whether or not employees who possess high levels of cultural intelligence (CI) are less or more likely to want to eave their job, and the effect of perceived organizational justice on the relationship between CI and turnover intention (TI) within the Lebanese hospitality and tourism sector. Design: Literature review, quantitative analysis, and a survey filled by 185 respondents via convenience sampling were conducted. The survey gathered demographic information about the service employees in the hospitality and tourism sector as well as answers pertaining to their level of CQ, POJ, and TI. The data obtained were then analyzed using the Statistical Package for Social Sciences SPSS (version 26) Descriptive and inferential statistics were administered. Findings: CI had a positive relationship with TI. POJ did not moderate the relationship between CI and TI. However, most of the respondents held low-end jobs and belonged to generation Y and Z (age group: 18-34). Originality: The study took place in Lebanon, a relatively under looked geographical area in research. Moreover, the fact that the study provides practical, theoretical and future research recommendations in the hospitality and tourism sector is a worthy addition for the world of research.